Capacity Building Overview of the Arctic Council - Lyen, Ron; Gregorich, Joan (Arctic Council Sustainable Development Working Group, 2004)
This guide provides a handy reference to the work of the Arctic Council for the many groups and individuals living and working in the Arctic or interested in circumpolar affairs. It is also a useful tool for the Council itself, helping researchers and other project participants to gain a wider view of the work of the Council, and making links between their projects and other activities. Project entries appear under three headings — Circumpolar/Regional Cooperation, Information for Decision Making, and Community Partnerships. Each entry includes a project title and brief description, a list of the project’s capacity-building elements, the Arctic Council working group or groups involved, and contact information for readers who want to find out more. In some cases a related publication is cited or a web site is given. Readers are also referred to the general web sites of the working groups, listed below. Also included in this guide is a list of acronyms that often come up in publications of the Arctic Council and its partners. An index at the end of the guide can be used to locate entries for specific projects. Contributing Bodies: Arctic Council, Arctic Council Working Group Secretariat – SDWG, AMAP, PAME, CAFF, ACIA, EPPR, ACAP Contributing Institutions: Natural Resources Canada, Foreign Affairs Canada, Ministry of the Environment Finland